(untitled) (Móin-Móin Magazine - Studies in the Art of Puppetry, 2022)
This article intends to discuss the potency, as well as the political and contravening dimension in Mamulengo’s play called Women’s Congress of the group Mamulengando Alegria of Glória do Goitá-PE, formed by Neide, Cida and Larissa Lopes. Our proposal is to compose a text in dialogue with Cida, reflecting an articulation with the theoretical reference of bell hooks (2019), Marcela Lagarde (2011), Margareth Rago (2013), Patrícia Dutra (1998) and Law 13.104, elucidating how the laughable is transformed in the face of the claims and social struggles of women in the 21st century, also thinking about the impacts that the production of shows like this reverberate on the public.